Molecular basis for the enzymatic inactivity of class III glutaredoxin ROXY9 on standard glutathionylated substrates - Pascal Mrozek; Stephan Grunewald; Katrin Treffon; Gereon Poschmann; Fabian Rabe von Pappenheim; Kai Tittmann; Christiane Gatz (Nature Communications)
Abstract Class I glutaredoxins (GRXs) are nearly ubiquitous proteins that catalyse the glutathione (GSH)-dependent reduction of mainly glutathionylated substrates. In land plants, a third class of GRXs has evolved (class III). Class III GRXs regulate the activity of TGA transcription factors through yet unexplored mechanisms. Here we show that Arabidopsis thaliana class III GRX ROXY9 is inactive as an oxidoreductase on widely used model substrates. Glutathionylation of the active site cysteine, a prerequisite for enzymatic activity, occurs only under highly oxidizing conditions established by the GSH/glutathione disulfide (GSSG) redox couple, while class I GRXs are readily glutathionylated even at very negative GSH/GSSG redox potentials. Thus, structural alterations in the GSH binding site leading to an altered GSH binding mode likely explain the enzymatic inactivity of ROXY9. This might have evolved to avoid overlapping functions with class I GRXs and raises questions of whether ROXY9 regulates TGA substrates through redox regulation.